In situ growth of g-C3N4 on TiO2 nanotube arrays: Construction of heterostructures for improved photocatalysis properties. Issue 1 (February 2020) - Sim, Lan Ching; Koh, Kai Sheng; Leong, Kah Hon; Chin, Yik Heng; Aziz, Azrina Abd; Saravanan, Pichiah
Graphical abstract: Highlights: Binary heterostructures are constructed via in situ growth of g-C3 N4 onto TNTs. Heterojunction at composite's interface facilitates oriented transfer of charges. The presence of g-C3 N4 enhanced the visible light harvesting properties of TNTs. Excessive introduction of urea up to 1.5 and 2 g diminished photodegradation of MB. g-C3 N4 /TNTs(1.0 g) performs the fastest degradation under visible light irradiation. Abstract: In this work, we successfully constructed g-C3 N4 /TNTs heterostructures via in situ growth of g-C3 N4 on the surface of TiO2 nanotube arrays (TNTs). Varying concentrations of urea precursor were adopted to prepare the binary composites for the photodegradation of methylene blue (MB). Advanced microscopic and spectroscopic approaches such as FESEM, PL-Raman, UV–vis DRS, XRD and etc examined the topography, structural and optical properties attributed to the presence of g-C3 N4 in the heterostructures. The morphological analysis showed that the in-situ growth of g-C3 N4 onto the surface of TNTs significantly increased the wall thickness of the nanotubes. The least band energy of 1.8 eV was obtained by g-C3 N4 /TNTs (1.5 g) due to the formation of an impurity energy level induced by the presence of g-C3 N4 . The electron transfer between the heterojunction of g-C3 N4 and TNTs was revealed by the quenching of PL emission intensity. When the urea content was optimized at 1.0 g, the build-in electric field at the interface of g-C3 N4 /TNTs stimulated the electrons transfer and prolonged lifetime of carriers, thus enhancing the degradation efficiency by 1.25 times higher than that of pure TNTs. However, the aggregation of g-C3 N4 as a result of increasing urea content (1.5–2.0 g) reduced the interfacial adhesion at the heterojunction between the g-C3 N4 and TNTs, thus dominating its excellent optical and charge separation properties and diminishing the degradation efficiency of MB.